2015
DOI: 10.1002/oby.21167
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of water preloading before main meals as a strategy for weight loss in primary care patients with obesity: RCT

Abstract: Objective: To investigate the efficacy of water preloading before meals as a weight loss strategy for adults with obesity. Methods: A two-group randomized controlled trial was conducted in Birmingham, England. Eighty-four adults with obesity were recruited from general practices. All participants were given a face-to-face weight management consultation at baseline (30 min) and a follow-up telephone consultation at 2 weeks (10 min). At baseline, participants were randomized to either drinking 500 ml of water 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…8 Although these crosssectional studies of water intake and obesity have shown mixed results, results from recent longitudinal studies and randomized controlled trials indicate the potential for water to prevent and treat obesity effectively. 4,9 Findings from 3 prospective cohort studies (the Nurses' Health Study I and II, and the Health Professionals Follow-Up Study) indicate that greater water intake is inversely associated with weight gain. 10 Among these studies, water intake has been the outcome of interest.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…8 Although these crosssectional studies of water intake and obesity have shown mixed results, results from recent longitudinal studies and randomized controlled trials indicate the potential for water to prevent and treat obesity effectively. 4,9 Findings from 3 prospective cohort studies (the Nurses' Health Study I and II, and the Health Professionals Follow-Up Study) indicate that greater water intake is inversely associated with weight gain. 10 Among these studies, water intake has been the outcome of interest.…”
Section: Introductionmentioning
confidence: 99%
“…10 Among these studies, water intake has been the outcome of interest. 4,[8][9][10] Urine osmolality, however, is a more effective measure of hydration than water intake alone, as it accounts for water and solutes acquired in food and other beverages. 11 Urine osmolality also measures daily water intake more accurately because it is an objective laboratory measurement that is not subject to recall bias.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations